Interoperabilità e accessibilità dei dati topografici. Integrazione, aggiornamento e generalizzazione delle banche dati della Regione Toscana - Ciampi, Christian; Lucchesi, Fabio; Nardini, Fabio; Scatarzi, Ilaria (Ri-Vista. Research for landscape architecture, 2015)
The Project that involves the Italian Institute “Centro Interuniversitario di Scienze del Territorio” and the Italian Regional Institution “Regione Toscana” is the background of the presented research that was activated to verify the potential use of Desktop GIS computer tools in map generalization. The large scale topographic map data stored in the Regional Database was processed using map generalization models and tools to create a small scale map useful to support landscape analysis and studies.